Konstruksi media massa terhadap pemberitaan illegal logging :: Analisis framing media cetak Kompas, Pontianak Pos, dan Riau Pos terhadap pemberitaan masalah illegal logging - ABDULGANI, Surya ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Many news in illegal logging case in Indonesia often becomes headline, even illegal logging often accused as the cause global warming. But each media reports on it according to their vision and mission. News tendency of a media can be seen from their frame. Aspects studied in this research is news about illegal logging, this research methods applies approach of constructivism by applying analysis textual consisted of by qualitative analysis in the form of framing analysis. Besides this research also applies intellectual analysis covering analysis produce texts, and socio-cultural by using Pan & Kosicki’s framing analysis. For the purpose in this research, takes three daily newspapers there are Pontianak Post, Riau Post, and Kompas. Hereinafter makes two big questions how frame applied by the daily three newspapers and what which background make difference of frame in the daily, and how news construction carried out by the newspapers. Result from this research indicates that tendency of news in mass media local as according to the importance more majoringly is local illegal logging and interrelationship with local goverment, differs from daily localness, Kompas is more view humanism side, with factual news and tells a story as it is.